Welfare states under pressure / edited by Peter Taylor-Gooby. - Taylor-Gooby, Peter (SAGE, 2001)
This is a timely and comprehensive review of welfare policy making in Europe. The text compares the different ways in which welfare states have responded to similar pressures over recent years and considers possible future developments.